Predictors of mortality in patients of poisonous snake bite: Experience from a tertiary care hospital in Central India - Chaudhari, Tejendra S (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND AND AIMS: This study was undertaken, to assess the clinical parameters in patients of poisonous snakebite, complications which occurred in them, their outcome and to evaluate various clinical predictors of mortality MATERIALS AND METHODS: Four hundred and thirty-two patients of snake bite were admitted, of which 172 did not show any signs of envenomation and excluded. Two hundred and sixty patients had signs of local or systemic envenomation and included. Complete clinical examination, blood counts, kidney function tests, serum electrolytes, coagulation profile was done in all patients. All received tetanus toxoid and anti-snake venom (ASV). Appropriate supportive treatment was given. Clinical and laboratory parameters were compared between patients who were discharged (Group A) and those who expired (Group B). All data analysis was performed by using stata software version 10 [StataCorp LP, Texas, USA] and SPSS version 11 [SPSS Inc, Chicago, USA]. RESULTS: Out of 260 patients, 58 died and 202 survived. Mean age was 34.97 ± 14.07 years. One hundred and eighty-six (71.5%) patients were from rural areas and 74 (28.5%) from urban. 63.4% of bites occurred during rainy season. One hundred and ninety-seven (75.8%) had bite on lower limb and 62 (23.8%) on upper limbs. All 260 patients (100%) had pain at site of bite, local swelling in 252 (96.9%) and blackening of skin, blebs in 18 (6.9%). Seventy-seven (29.6%) had bleeding tendencies. Ptosis was present in all the 65 patients with signs of neuroparalysis. Eighty (30.8%) patients had acute renal failure. The mean duration of stay in survivors was 7.50 + 4.13 days and in non-survivors it was 3.45 + 3.02 days. Out of 58 who died 18 (31%) patients, succumbed within 24 hrs. On multivariate analysis, significant predictors o mortality were bleeding tendency (P = 0.013), mean PTTK (sec) (P = 0.047), respiratory failure (P = 0.045), shock (P = 0.013), mean ASV dose (cc) (P < 0.001). CONCLUSIONS: Mortality in patients with snake bite can be predicted by simple variables like presence of bleeding tendencies, respiratory failure, and shock. These parameters can help the doctors at peripheral health centers to predict outcome, so that such high risk cases can be referred to higher centers for expertise management without wasting time.